Efficacy of anthracycline/taxane‐based neo‐adjuvant chemotherapy on triple‐negative breast cancer in BRCA1/BRCA2 mutation carriers. Issue 3 (19th September 2017) - Bignon, Lucie; Fricker, Jean‐Pierre; Nogues, Catherine; Mouret‐Fourme, Emmanuelle; Stoppa‐Lyonnet, Dominique; Caron, Olivier; Lortholary, Alain; Faivre, Laurence; Lasset, Christine; Mari, Veronique; Gesta, Paul; Gladieff, Laurence; et al.
Abstract: This study aims to estimate the pathologic complete response (pCR) rate after neo‐adjuvant chemotherapy and to compare disease‐free survival (DFS) and overall survival (OS) between pCR and non‐pCR groups of patients with triple‐negative breast cancer (TNBC) and deleterious BRCA1 or BRCA2 mutation. We carried out a retrospective analysis of 53 patients including 46 BRCA1, 6 BRCA2, and 1 combined BRCA1 and BRCA2 mutation. All patients had been diagnosed with triple‐negative breast cancer (TNBC) between 1997 and 2014. Neo‐adjuvant therapy consisted of regimens that were based on anthracycline or an anthracycline‐taxane doublet. DFS included any relapse or second cancer. The Kaplan‐Meier method and the log‐rank test were used to compare pCR and non‐pCR groups. A pCR was observed in 23 (42.6% [95% CI, 29.2%‐56.8%]) of the TNBC included. The pCR rate was 38.3% [95% CI, 26%‐55%] among BRCA1 mutation carriers, and 66% among the 6 BRCA2 mutation carriers. Median follow‐up was 4.4 years (range 0.62‐16.2 years) and did not differ between the groups ( P  = .25). Fifteen relapses and six second cancers were recorded during the follow‐up period. Eleven deaths occurred, all of which were in the non‐pCR group. DFS ( P  < .01) and OS ( P  < .01) were significantly better in the pCR group than the non‐pCR group. This study shows a high pCR rate after neo‐adjuvant therapy in BRCA ‐mutated triple‐negative breast cancer, and the survival results confirm the prognostic value of pCR in this group. These outcomes should be considered as a basis of comparison to be used by future studies about new therapies in this domain.